Structural chemistry and electronic properties of the n=3 Ruddlesden-Popper phases Ca4Mn2FeO9.75 and Sr4Mn2FeO9.80 - Battle, P; Branford, W; Mihut, A; Rosseinsky, M; Singleton, J; Sloan, J; Spring, L; Vente, J (1999)
The room-temperature crystal structures of the n = 3 Ruddlesden-Popper phases Ca4Mn2FeO9.75 and Sr4Mn2FeO9.80 have been refined from neutron and X-ray powder diffraction data. Both adopt space group 14/mmm with (a,c) = (Ca, 3.73683(1), 27.0860(1) ̊), (Sr, 3.83393(1), 27.8148(1) ̊). In both compounds the cation site at the center of the perovskite blocks is preferentially occupied by Fe (Ca, Mn:Fe = 0.424:0.576(4)), and the anion vacancies are found around this site. The occupied anion sites show static disorder in Ca4Mn2FeO9.75 but not in Sr4Mn2FeO9.80. Both compounds are electrical insulators which order antiferromagnetically at TN = 75 K (Ca) or 90 K (Sr). Susceptibility and M(H) data suggest that not all the Mn and Fe cations take part in the long-range magnetic ordering, and there is evidence of a spin glass transition in both compounds at ̃11 K. The magnetic structure of Ca4Mn2FeO9.75 at 5 K has been determined by neutron diffraction. No ordered moment was detected on the Mn/Fe site at the center of the perovskite blocks; 0.74(1) μB per transition metal cation was measured at the sites on the block edges. Possible causes of magnetic frustration in this crystal structure are considered. Ca4Mn2FeO9.75 has a magnetotresistance of -4% at 137 K in a 14 T field. © 1999 American Chemical Society.